ANALISIS FAKTOR-FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN RUAM POPOK PADA BAYI DAN BALITA DI KELURAHAN TANJUNG BUNTUNG - Sudarsono; Nopri Esmiralda; Eshan Ratu Azzahra (Universitas Batam, 2024)
Background: Diaper rash (diaper dermatitis) is an inflammatory eruption in the area covered by diapers. The usual initial symptoms of diaper rash are mild redness in the area around the use of diapers that is limited in nature accompanied by abrasions or minor wounds on the skin, shiny, sometimes similar to burns and wetness, red spots and swelling in the area most exposed to diapers. Method: This study is an observational analytic study using a cross sectional approach conducted in Tanjung Buntung Subdistrict, the work area of the Tanjung Buntung Health Center, Batam City in December 2023. The sampling technique was accidental sampling technique with a total sample size of 60 respondents. The data analysis used was univariate analysis and bivariate analysis with the Chi-Square test Result: From the results of the study, it was found that the type of diaper, frequency of changing diapers, and diarrhea had an association with the incidence of diaper rash. The results of the Chi-Square statistical test obtained a p value for the type of diaper with the incidence of diaper rash 0.036 (<0.05), the p value for the frequency of changing diapers with the incidence of diaper rash 0.042 (<0.05), and the p value for diarrhea with the incidence of diaper rash 0.000 (<0.05). Conclusion: Based on this study, there is a relationship between diaper type, frequency of diaper changing, and diarrhea with the incidence of diaper rash in infants and toddlers in Tanjung Buntung Subdistrict. Keywords: Diapers, Diarrhea, Diaper Rash